Homogeneous coil design for wireless charging electric vehicles - Ahmad, Ahmad Muhamed; Khalifa, Othman Omran; Najeeb, Athaur Rahman (IJARIIE, 2022)
Electric vehicles are slowly becoming the first option for the consumers as by the time goes the challenges that are limiting the chances of its existence are being reduced due to the efforts of all the researchers on the idea of having a green world as much as possible by eliminating any source ofpollution that found a green replacement. However, the performance of the electric vehicles is not enough to make an industrial change while there are challenges that are yet to be solved additionally the main problem is the time taken to have the battery fully charged in both ways static and dynamic charging. However, for the static charging the time is rapidly being enhanced due to the enhancement in the fast charging cable improvements but for the dynamically charging it’s all about the efficiency of the connection during the power transmission. In this paper, a homogenous coil has been designed and tested under different conditions in order to obtain the best record of the efficiency. lastly an enhanced method has been produced to wirelessly charge the electric vehicle with the help of the homogeneous pads.